Rise and Fall of the Christian Democrats’ Movement in Poland after 1989 - Sowa, Kazimerz Z. (2008)
This article sets out to explain why Poland has not been successful in establishing a Christian political party...this in the face of the overwheming evidence of religiosity in the Polish national ethos. Drawing on historical and cultural elements, it details a Polish reluctance to link together Church and State so thoroughly when religion already influences the State in other less-overt political ways.
Keywords: Christian Democratic Movement; Polish church